Achilles tendon and enthesis assessment using ultrashort echo time magnetic resonance imaging (UTE-MRI) T1 and magnetization transfer (MT) modeling in psoriatic arthritis - Moazamian, Dina; Athertya, Jiyo S.; Dwek, Sophia; Lombardi, Alecio F.; Mohammadi, Hamidreza Shaterian; Sedaghat, Sam; Jang, Hyungseok; Ma, Yajun; Chung, Christine B.; Du, Jiang; Jerban, Saeed; Chang, Eric Y. (NMR in biomedicine, 2023)
The purpose of this study is to investigate the use of ultrashort echo time (UTE) magnetic resonance imaging (MRI) techniques (T1 and magnetization transfer [MT] modeling) for imaging of the Achilles tendons and entheses in patients with psoriatic arthritis (PsA) compared with asymptomatic volunteers. The heels of twenty-six PsA patients (age 59 ± 15 years, 41% female) and twenty-seven asymptomatic volunteers (age 33 ± 11 years, 47% female) were scanned in the sagittal plane with UTE-T1 and UTE-MT modeling sequences on a 3-T clinical scanner. UTE-T1 and macromolecular proton fraction (MMF; the main outcome of MT modeling) were calculated in the tensile portions of the Achilles tendon and at the enthesis (close to the calcaneus bone). Mann-Whitney-U tests were used to examine statistically significant differences between the two cohorts. UTE-T1 in the entheses was significantly higher for the PsA group compared with the asymptomatic group (967 ± 145 vs. 872 ± 133 ms, p < 0.01). UTE-T1 in the tendons was also significantly higher for the PsA group (950 ± 145 vs. 850 ± 138 ms, p < 0.01). MMF in the entheses was significantly lower in the PsA group compared with the asymptomatic group (15% ± 3% vs. 18% ± 3%, p < 0.01). MMF in the tendons was also significantly lower in the PsA group compared with the asymptomatic group (17% ± 4% vs. 20% ± 5%, p < 0.01). Percentage differences in MMF between the asymptomatic and PsA groups (−16.6% and −15.0% for the enthesis and tendon, respectively) were higher than the T1 differences (10.8% and 11.7% for the enthesis and tendon, respectively). The results suggest higher T1 and lower MMF in the Achilles tendons and entheses in PsA patients compared with the asymptomatic group. This study highlights the potential of UTE-T1 and UTE-MT modeling for quantitative evaluation of entheses and tendons in PsA patients.